Tourism destinations and tourist behavior based on community interaction models of film-enabled tourism destinations - Lao, Yongshi; Zhu, Jianfei; Liu, Jinlin (Frontiers in Psychology, 2023)
It is widely recognized by the industry and academia that the integration and collaboration of film elements is an effective pathway for the innovative development and experience upgrading of cultural tourism industry. Previous studies discussed primarily the cultural tourism development mechanism of tourist destinations from the perspective of tourist destinations and tourist experience but rarely explored the cultural tourism development mechanism in the film-enabling context from the perspective of interest-related community interaction. The current study has conducted high-frequency word analysis and element category analysis towards the online text data of the Japanese animation film Your Name from the angle of interest-related community interaction by means of online text analysis and Grounded Theory analysis, and proposed the elements of interest-related community interaction in cultural tourism triggered by the film including tourist hotspots, tourism resources, tourist experience, sightseeing expectations, tourism evaluation and information dissemination, and formulated the orientation pathway of film-enabling cultural tourism based on the interest-related community interaction. The current study aims to enrich the cultural tourism research and provide theoretical support and reference for film-enabling cultural tourism in the Internet era by means of introducing the concept of interest-related community innovatively into the scene of film-enabling cultural tourism.